The role of knowledge maps in supporting talent management: Analytical study of the opinions of a sample of workers in the Al-Kafeel Specialist Hospitals and Al-Hujjah Charitable Hospitals - فيصل علوان الطائي; فرقان هادي العبادي (Iraqi Journal for Administrative Sciences, 2024)
The research sought to know the role that knowledge maps play in their dimensions (Signs of individual knowledge, Domain Topic Selection, Inter Domain Topic Association Analysis) according to (Liu & et al., 2009) in talent management and its dimensions (attraction, development, performance management, retention) according to (Osinga, 2009) scale by examining a sample of workers in the searched hospitals, as a questionnaire was distributed to a sample of (225) individuals representing workers in the medical, nursing and administrative specialties. The simple correlation coefficient was used to measure the correlation relationship between the variables, and a (t) test to find out The significance of the simple correlation relationship, and modeling the structural equation to test the main direct effect hypothesis and the sub-hypotheses emanating from it, and using advanced statistical programs such as (SPSS V.24 and Amos V. 23)), and the researcher reached a number of conclusions, the most important of which is (the existence of a relationship A strong positive correlation between knowledge maps in their dimensions and talent management) and the most important recommendations (the need to pay attention to knowledge maps for their role in supporting talent management by establishing a unit for knowledge maps in the human resources management department in hospitals, the research sample).